Analysis of temperature-dependent layered shells subjected to thermomechanical loading. Issue 26 (26th October 2022) - Zhang, Zhong; Zhou, Ding; Fang, Hai; Huo, Ruili
Abstract: An analytical method is proposed for the analysis of simply supported temperature-dependent layered shells subjected to thermomechanical loading. The method is developed by introducing a sublayer model: assuming each layer of the shell comprises numerous fictitious sublayers, and the material properties of each sublayer are uniform. Based on this model, an iterative procedure is used to predict the radial temperature distribution; the transfer-matrix technique is used to predict the displacement and stress distributions based on the three-dimensional thermoelasticity theory. Some examples are provided to study the effects of surface temperature and material properties on the thermomechanical performances of a three-layer shell.